2014
DOI: 10.1097/ico.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Corneal Thickness Monitoring During Corneal Collagen Cross-Linking With Isotonic Riboflavin Solution With and Without Dextran

Abstract: Using isoosmolar riboflavin solution without dextran causes a steady increase in the corneal thickness during the cross-linking procedure, as opposed to riboflavin with dextran. This result might be beneficial in broadening the spectrum of cross-linking indications in patients with thin corneas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…Previous studies and the standard CXL procedure have generally used an iso-osmolar riboflavin 0.1% solution containing 20% dextran (402.7 mOsmol/L), which exerts a temporary dehydrating effect and consequent corneal thinning. In contrast, we performed the CXL procedure with a dextran-free isotonic riboflavin solution and observed that the corneal thickness increased throughout the procedure, in agreement with the results of a previous study (14) . However, the safety CXL in the presence of an artificially swollen cornea remains con troversial because the lower concentration of collagen fibers in the hydrated stroma is expected to weaken the crosslinking effect of UVA, as demonstrated in experiments with collagen gels (15) .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Previous studies and the standard CXL procedure have generally used an iso-osmolar riboflavin 0.1% solution containing 20% dextran (402.7 mOsmol/L), which exerts a temporary dehydrating effect and consequent corneal thinning. In contrast, we performed the CXL procedure with a dextran-free isotonic riboflavin solution and observed that the corneal thickness increased throughout the procedure, in agreement with the results of a previous study (14) . However, the safety CXL in the presence of an artificially swollen cornea remains con troversial because the lower concentration of collagen fibers in the hydrated stroma is expected to weaken the crosslinking effect of UVA, as demonstrated in experiments with collagen gels (15) .…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, we reported that the use of a dextran-free iso-osmolar riboflavin solution during CXL induced a steady increase in corneal thickness throughout the procedure. This finding might be beneficial with respect to an in creased indication for CXL in patients with thin corneas, as it removes the concern of unpredictable intraoperative thinning below the sa fety margin reported in our other study (14) . We note that the impro vements in visual acuity and keratometry readings were found to occur progressively throughout the postoperative follow-up pe riod, suggesting that a longer follow-up is needed to determine the total functional and anatomic effects of CXL and to obtain stable functional and keratometric values.…”
Section: Discussionmentioning
confidence: 89%
“…Using methylcellulose rather than dextran in the riboflavin solution has the advantage of increasing intraoperative central corneal thickness (CCT) during CXL (Oltulu et al. ; Zaheer et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have utilized isoosmolar riboflavin without Dextran to allow corneal thickening [20]. For all iatrogenic thickened corneas, concern exists for safety and efficacy.…”
Section: Corneal Cross-linking Safety Parametersmentioning
confidence: 99%